OC-089 One-year experience of a hepato-pancreatobiliary cancer service in a large district general hospital: impact on local cancer care delivery. (23rd September 2015) - Kia, R; Boon, A; Faizallah, R; Singhal, A
Abstract : Introduction: Dedicated hepato-pancreatobiliary (HPB) cancer teams are rare outside tertiary centres. Patients with HPB cancer pose complex clinical problems requiring close liaison between primary, secondary and tertiary care. Reconfiguration of HPB cancer services in the Mersey region has lead to standardisation of care via referral to Regional Specialist Centres (RSC). However, local cancer care delivery remains fragmented and limited by the variable expertise of various clinical teams involved. We report the impact of a new combined consultant and nurse-led service established to improve overall management and facilitate local ownership of care. Methods: Our local HPB cancer service (HPBCS) was established on 1 June 2008, the first of such service in a large DGH (catchment population: 360 000) in the Mersey region. All patients with suspected HPB cancer were referred to the local HPB Team comprising of two consultants with interest in HPB diseases (one nominated lead clinician) and a nurse specialist. Patients were case managed as per the Mersey and Cheshire Cancer Network Protocol, with discussion at the appropriate RSC MDT meetings (pancreas and hepatobiliary). The local HPBCS team meets weekly to discuss all new referrals, MDT outcomes and urgent management issues. There is also a weekly HPB nurse-led clinic that provides urgent feedback of RSC decisions, rapid access for symptom control and ensures continuity of care. Results: 279 patients were referred to the HPBCS between 1 June 08 and 1 June 09: 175 for suspected pancreatic cancer (PC), 104 for hepatobiliary cancer (HC). This compares with 51 for suspected PC over a 6-month period pre-HPBCS and 26 for suspected HC a year pre-HPBCS, representing an annual increase of 72% and 300%, respectively. The outcomes of discussion at the RSC for suspected PC were: inoperable PC (59/175), operable PC (24/175), IPMN (45/175), benign lesions (22/175), pancreatitis (15/175) and pseudocysts (10/175), while for HC: hepatocellular carcinoma (34/104), gallbladder cancer (13/104), cholangiocarcinoma (9/104), liver metastases of unknown primary (2/104), benign liver lesions (23/104) and liver lesions of unknown significance (21/104). 23.7% of cases (45 IPMN, 21 liver lesions of unknown significance) were referred back for local surveillance contributing to an ever expanding pool of patients under the local HPB team. Nearly all cases were referred to the RSCs within 2 weeks of referral. Conclusion: (1) Since commencement of HPBCS, there is a sharp increase of suspected HPB cancers identified and referred on to RSCs, leading to timely and uniform care as per regional network guidelines. (2) All Wirral patients with suspected HPB cancer are now case managed by the HPBCS with local ownership of care.